RANCANG BANGUN SISTEM INFORMASI AKADEMIK MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) (Studi Kasus : MI UMMUL QURO) - Sita Khoerunisa (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
MI Ummul Quro is one of the Ibtidaiyah madrasas located in Pondok Cabe Ilir, Pamulang, South Tangerang - Banten. have been filled in, as well as in student data collection such as grades and others, this school still uses a manual system which is of course very time consuming. To be able to help solve these problems by presenting an application that can be used by madrasas to be able to manage academic data properly.The rapid application development (RAD) method is a development cycle designed to provide much faster development and higher quality results than is achieved with traditional life cycles.With the application of an academic information system, it can make it easier to register new students without having to go to school and produce a system that can make it easier for teachers and homeroom teachers to record attendance, lesson scores faster and more efficiently